Optical characteristics of traditional elastic andn rigid fresnel microprisms - Petrov, V. V.; Antonov, E. E.; Kryuchyn, A. A.; Shanoilo, S. M. (Інститут проблем реєстрації інформації НАН України, 2015)
The dependence of the resolution of images formed by Fresnel microprisms elements on the prismatic strengths of such elements has been investigated. The relative optical characteristics of monoprisms and microprisms by different manufactures have been obtained. The algorithm of vision acuity determination has been modernized from the resolution ability of test images. Fig.: 12. Refs: 10 titles.